2010
DOI: 10.4292/wjgpt.v1.i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiocirculatory pathophysiological mechanisms in severe acute pancreatitis

Abstract: Acute pancreatitis (AP) is a common and potentially lethal acute inflammatory process. Although the majority of patients have a mild episode of AP, 10%-20% develop a severe acute pancreatitis (SAP) and suffer systemic inflammatory response syndrome (SIRS) and/or pancreatic necrosis. The main aim of this article is to review the set of events, first localized in the pancreas, that lead to pancreatic inflammation and to the spread to other organs contributing to multiorganic shock. The early pathogenic mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
(70 reference statements)
0
3
1
1
Order By: Relevance
“…nitric oxide) and vasoconstrictor (endothelin and angiotensin) mediators have been proposed. 36 Respiratory failure was the most common systemic complication in our study and there was also no significant difference in the incidence of systemic complications in both biliary and non-biliary groups, but there was some variation in the incidence systemic complications as compared with other studies. 21 The need of intervention depends on the type of complications that develops after an episode of AP.…”
Section: Jssn 2017; 20 (1)contrasting
confidence: 40%
“…nitric oxide) and vasoconstrictor (endothelin and angiotensin) mediators have been proposed. 36 Respiratory failure was the most common systemic complication in our study and there was also no significant difference in the incidence of systemic complications in both biliary and non-biliary groups, but there was some variation in the incidence systemic complications as compared with other studies. 21 The need of intervention depends on the type of complications that develops after an episode of AP.…”
Section: Jssn 2017; 20 (1)contrasting
confidence: 40%
“…In summary, patients with SAP are frequently characterized by a severe hypovolemic and distributive shock, which ultimately leads to the development of MOF [ 23 25 ]. The extent of fluid depletion/shifts is, however, difficult to assess precisely.…”
Section: Hypovolemia and Organ Failurementioning
confidence: 99%
“…The pathogenic mechanism, pathologic process and management of SAP have yet to be completely clarified. Thus, the incidence of serious complications of SAP and morbidity rates could not be substantially decreased (8,(10)(11)(12). Previous studies showed that NF-κB plays a critical role in the clinical course of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%